Upaya Penurunan Gap Antara Job Demands dan Job Resources: Studi Kasus di Sebuah Perusahaan Shipping Logistics - Rudy Darmawan; Prayonne Adi; I Nyoman Sutapa (Jurnal Titra, 2021)
The article discusses a job demands and job resources at a shipping logistics company. Jobs related to ships and logistics tend to have bigger problems compared to regular workers. This research focuses on seeing the job demands or the work pressure that the workers feel, the job resources or the support that the company gives, and the gap between the company’s and worker’s point of view regarding the job demands and job resources the company gave and the worker received. To see the amount of job demands and job resources, a questionnaire is made with various questions related to job demands and job pressures that has answer options of likert scale 1-5. Job demands with a value bigger than 3 and the gap that is more than 1 between the company’s and worker’s point of view will be analyzed to look for their causes and make the suggestions. The suggestions are made to reduce the tension the workers get from working or the job demands and to balance the tension and support that the workers receive and the company gives